Work Participation after Multimodal Rehabilitation due to Cardiovascular Diseases - Representative Analyses using Routine Data of the German Pension Insurance - Streibelt, Marco; Zollmann, Pia; Völler, Heinz; Falk, Johannes; Salzwedel, Annett (Die Rehabilitation, 2024)
Cardiovascular diseases represent a large proportion of the disease burden of the adult population in Germany. Their importance in rehabilitation has increased continuously in recent years. Several studies have investigated return to work of cardiac patients after rehabilitation, which is relevant from the perspective of pension insurance. However, there is a lack of representative findings for the German region on employment trajectories and their influencing factors. The rehabilitation statistics database of the German Pension Insurance (GPI) was used for this study. Subjects were patients with cardiovascular diseases undergoing rehabilitation in 2017. Analyses were performed for the total group and differentiated by relevant diagnosis groups. Occupational participation was operationalized via a monthly state variable up to 24 months after rehabilitation and the rate of all persons who were employed at the 12- and 24- month follow-up and in the 3 months before, respectively. Multiple logistic regression models were calculated to analyze the influencing factors. The total sample comprised 59,667 patients. The average age in all groups was between 53 and 56 years. Men were disproportionately represented; 70% of the services were provided as follow-up rehabilitations and 88% in the inpatient setting. Stable employment rates were 66% after one year and 63% after two years in the overall group (disease groups: 49% to 71%). The strongest influencing factors were the amount of pay and the number of sickness absence days before rehabilitation, active employment before rehabilitation, and age. For the first time, representative data on occupational participation following rehabilitation on behalf of the GPI are available for the disease groups considered. The analyses underline the need to focus on occupational perspectives already in medical rehabilitation or directly thereafter.